Juridical Review of the Crime of Transferring the Object of Fiduciary Guarantee Without the Consent of the Fiduciary Recipient - George Johanes Paulus; Noenik Soekorini; M. Syahrul Borman (Civiliza Publishing, 2026)
This study examines the criminal act of transferring fiduciary collateral objects without the prior written consent of the fiduciary recipient as regulated under Indonesian law. The rapid development of consumer financing practices has increased the use of fiduciary guarantees, particularly in credit agreements involving movable assets. However, in practice, debtors often transfer, pledge, or lease fiduciary objects to third parties without authorization, which constitutes a criminal offense under Law Number 42 of 1999 on Fiduciary Security. This research employs a normative juridical method with a statutory approach, analyzing primary legal materials in the form of legislation and court decisions, as well as secondary legal materials from legal literature and scholarly works. The study focuses on the regulation of such criminal acts and the form of criminal liability imposed on fiduciary grantors who violate fiduciary provisions. The findings indicate that the transfer of fiduciary collateral without the consent of the fiduciary recipient fulfills the elements of a criminal offense as stipulated in Article 36 of the Fiduciary Security Law. Criminal liability may be imposed if the perpetrator is proven to have acted unlawfully, intentionally or negligently, and without any justification or excuse that eliminates criminal responsibility. This research concludes that the existing legal framework provides legal certainty and protection for creditors, although stricter supervision and legal awareness are necessary to prevent recurring violations in fiduciary practices.